Analisis Kelengkapan Berkas Rekam Medis Pasien Covid-19 Di Rumah Sakit Santa Elisabeth Medan Tahun 2021 - Jev Boris; Nasipta Ginting; Nurniat Oktoberniwati Gulo (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The hospital is an organization engaged in the health sector whose function is to provide plenary services. Medical record is a file that contains all records of patient identity documents and all services provided to patients in a health care facility. A complete medical record is a quality image of a hospital. The purpose of this study was to analyze the completeness of the medical record files for Covid-19 patients on patient identity sheets, anamnesis, informed consent, CPPT, medical resumes at Santa Elisabeth Hospital Medan 2021. The type of research used was descriptive retrospective research. The population in this study were medical record files for Covid-19, consisting of 930 medical record files. The sample in this study was as many as 87 medical records. Sampling was carried out by using Systematic Random Sampling method. The instrument used is a checklist sheet. The results showed that the percentage of completeness for the patient's identity medical record was 90,80%, the file was completely filled, the anamnesis was 97,70%, the file was completely filled, informed consent was 94,25%, the file was completely filled, CPPT was 93,10%, the file was completely filled, medical resume of 90,80% the file is completely filled. The conclusion drawn from this study is that most of the medical record files analyzed were completely filled out. The cause of the incomplete filling of the medical record file was due to the staff's inaccuracy in writing down patient data. It is expected that medical record officers need to have awareness and discipline in completing medical records by means of good cooperation between the nurse and the doctor concerned